2021
DOI: 10.7895/ijadr.289
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use among sexual minority women: Methods used and lessons learned in the 20-Year Chicago Health and Life Experiences of Women Study

Abstract: Background: Two decades ago, there was almost no research on alcohol use among sexual minority women (SMW, e.g., lesbian, bisexual). Since then, a growing body of scientific literature documents substantial sexual orientation-related disparities in alcohol use and alcohol-related problems. Research has identified multiple risk factors associated with high-risk/hazardous drinking among SMW. However, this research has almost exclusively used cross-sectional designs, limiting the ability to draw conclusions about… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 35 publications
2
15
0
Order By: Relevance
“…Consistent with our prior research, women who identified as mostly heterosexual, only heterosexual, or other were also excluded from analyses, leaving a final sample of 695. Data were collected using computer‐assisted in‐person or telephone interviews (Hughes et al, 2021). The Institutional Review Board of the University of Illinois at Chicago (UIC) approved study procedures.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with our prior research, women who identified as mostly heterosexual, only heterosexual, or other were also excluded from analyses, leaving a final sample of 695. Data were collected using computer‐assisted in‐person or telephone interviews (Hughes et al, 2021). The Institutional Review Board of the University of Illinois at Chicago (UIC) approved study procedures.…”
Section: Methodsmentioning
confidence: 99%
“…Data are from Wave 3 of the Chicago Health and Life Experiences of Women (CHLEW) study (see Hughes et al, 2021 for more details), a community‐based, 21‐year, five‐wave longitudinal study of SMW aged 18 and older. Wave 3 data were collected in 2010 to 2012 ( N = 353 women were retained [response rate = 79%] from the original cohort).…”
Section: Methodsmentioning
confidence: 99%
“…The procedures for each wave have been reviewed and approved by the institutional review board of the university where the principal investigator (TLH) held her primary appointment (waves 1-5 by the University of Illinois at Chicago; waves 4 and 5 and this study by Columbia University). Detailed information about the CHLEW study methods can be found elsewhere [ 58 , 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Other retention strategies included birthday and holiday cards, reminder calls before interview appointments, and graduated monetary incentives—from US $35 in wave 1 to US $80 in this study (US $40 for the telephone interview, US $20 for the web-based self-administered survey, and US $20 if the participant and their partner can be interviewed within 7 days of each other). Of the 820 participants enrolled in CHLEW (as of the writing of the grant application for this study), 49 (6.0%) were deceased, dropped out of the study, or were unable to participate for health reasons, leaving a sample size of 771 (94.0%) [ 59 ].…”
Section: Methodsmentioning
confidence: 99%
“…Data collection began in 2000 with 447 English-speaking women, Ages 18 and older, who self-identified as only or mostly lesbian or bisexual at baseline. Data collection for Wave 2 occurred in 2004-2005 and Wave 3 in 2010-2012 (see Hughes et al, 2021, for a comprehensive review of methods). The study was approved by the human subjects board at the university of the primary investigator.…”
Section: Participants and Proceduresmentioning
confidence: 99%